The diversity of planetary system architectures: contrasting theory with observations - Miguel, Yamila (2011)
In order to explain the observed diversity of planetary system architectures and relate this primordial diversity to the initial properties of the discs where they were born, we develop a semi-analytical model for computing planetary system formation. The model is based on the core instability model for the gas accretion of the embryos and the oligarchic growth regime for the accretion of the solid cores. Two regimes of planetary migration are also included. With this model, we consider different initial conditions based on recent results of protoplanetary disc observations to generate a variety of planetary systems. These systems are analysed statistically, exploring the importance of several factors that define the planetary system birth environment. We explore the relevance of the mass and size of the disc, metallicity, mass of the central star and time-scale of gaseous disc dissipation in defining the architecture of the planetary system. We also test different values of some key parameters of our model to find out which factors best reproduce the diverse sample of observed planetary systems. We assume different migration rates and initial disc profiles, in the context of a surface density profile motivated by similarity solutions. According to this, and based on recent protoplanetary disc observational data, we predict which systems are the most common in the solar neighbourhood. We intend to unveil whether our Solar system is a rarity or whether more planetary systems like our own are expected to be found in the near future. We also analyse which is the more favourable environment for the formation of habitable planets. Our results show that planetary systems with only terrestrial planets are the most common, being the only planetary systems formed when considering low-metallicity discs, which also represent the best environment for the development of rocky, potentially habitable planets. We also found that planetary systems like our own are not rare in the solar neighbourhood, its formation being favoured in massive discs where there is not a large accumulation of solids in the inner region of the disc. Regarding the planetary systems that harbour hot and warm Jupiter planets, we found that these systems are born in very massive, metal-rich discs. Also a fast migration rate is required in order to form these systems. According to our results, most of the hot and warm Jupiter systems are composed of only one giant planet, which is also shown by the current observational data.